2015
DOI: 10.1111/eos.12183
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of dental equipment to interfere with cardiac implantable electrical devices

Abstract: Lahor-Soler E, Miranda-Rius J, Brunet-Llobet L, Sabat e de la Cruz X. Capacity of dental equipment to interfere with cardiac implantable electrical devices. Eur J Oral Sci 2015; 00: 000-000. © 2015 Eur J Oral SciPatients with cardiac implantable electrical devices should take precautions when exposed to electromagnetic fields. Possible interference as a result of proximity to electromagnets or electricity flow from electronic tools employed in clinical odontology remains controversial. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…The results of the bivariate analysis referring to electromagnetic interference, adjusted according to the dental equipment tested, are summarized in Table . The results for the variables CIED type/make, application distance (dA), application time (tA), state of the insulation of the electrode leads, and dental equipment for all CIEDs, were reported in detail in the first part of the study .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of the bivariate analysis referring to electromagnetic interference, adjusted according to the dental equipment tested, are summarized in Table . The results for the variables CIED type/make, application distance (dA), application time (tA), state of the insulation of the electrode leads, and dental equipment for all CIEDs, were reported in detail in the first part of the study .…”
Section: Resultsmentioning
confidence: 87%
“…At present there is some controversy in the literature with respect to the effect of the possible interference of such electronic equipment with PMs and/or ICDs. However, in the first part of this investigation, following the same protocol, it was concluded that dental equipment tested at a clinical application distance (20 cm) provoked only slight interference in the CIEDs analysed .…”
mentioning
confidence: 99%
“…A total of 445 studies were excluded, and the full-text of 15 studies were assessed for eligibility. Among these 15 articles, seven fulfilled the inclusion criteria: five in vitro [1,3,10,15,20]; and two in vivo [21,22] studies. Figure 1 summarizes the details and results of the search strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of each study included in this review was given a grad out of 9. Four in vitro studies [1,3,15,20] reported that electronic apex locators do not interfere with cardiovascular implantable electronic devices and can be used safely. One in vitro study [10], however, reported that electronic apex locators caused electromagnetic interference without altering cardiovascular implantable electronic devices function and suggested that electronic devices should be kept to use at minimum distances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation